Perceived causes, exposures and adjustments to seasonal heat in different residential areas in Ibadan, Nigeria (2012)
Local perception can be an important resource for assessing and managing climate-related extremes and identifying adjustment strategies unique to specific settings. The objectives of the study are two-fold. Firstly, it examined the perceived causes, exposures and adjustments to seasonal heat events using different residential density areas of Ibadan, Nigeria, as spatial units of analysis. Secondly, it investigated the relationship between heat exposure, built environment, socio-economic and cultural factors. Results show that intense heat from the sun, climate change and absence of rains, among others, was identified as perceived causes. Number of electricity hours, distance from water supply points and the number of neighborhood trees were listed as the three most important factors affecting heat exposure. In addition, there were considerable variations in the perceived causes (F = 4.86, p<0.05), in exposures (F = 3.61, p<0.05), and in adjustments to seasonal heat (F = 8.75, p<0.05) across different residential density areas in Ibadan, Nigeria. The study demonstrates that local knowledge based on the perceptions, exposures and adjustments to seasonal heat waves has the potential in some cases to provide valid inputs into vulnerability and adaptation assessments.